PROSES PRODUKSI PEMANFATAAN LIMBAH PELEPAH BATANG POHON PISANG UNTUK AKSESORIS KEPALA DI DAERAH KAUJON BANTEN - Hidayat Sirruhu; Vania Aqmarani Sulaiman (Narada : Jurnal Desain dan Seni, 2020)
Banana tree trunk waste is considered as wasted material rather than being used as a material with high economic value. whereas the banana tree trunk waste is a material that is easily found in the community or villages, so it does not rule out the possibility of utilizing this banana trunk waste as head material. This study aims to try to find more value from banana tree trunk waste to be used as a head accessory, by utilizing banana tree trunk waste as material, the head accessories that will be made are brooch patches, headpieces, bandanas, and hats. The study was conducted to determine the production process of the utilization of banana tree trunk waste for the head accessories. The method used is the method of observation to the banana tree stem midrib to find out the production process from the beginning to become a product, this production process uses weaving technique. The product that will be produced in the process of producing banana tree trunk waste is in the form of head accessories, namely brooch patch, headpiece, bandana, and hat. The results of research on the production process of banana tree trunk waste can reduce waste and can become a renewable resource into the utilization of banana tree trunk waste. The resulting product can be ahead of the accessory product and increase the economic and aesthetic value and function of the waste.